For the Community, By the Community: Working with Youth to Understand the Physical Activity-Environment Relationship in First Nations Communities - Baillie, Colin PT; Johnson, Ashley M; Drane, Shannon; LePage, Ron; Whitecrow, Darcy; Lévesque, Lucie (Youth Engagement in Health Promotion, 2016)
Introduction: Physical activity participation benefits First Nations youth. Environmental factors like land-use mix influence physical activity opportunities available to youth. While the physical activity-environment link in urban centres is well understood, there has never been an exploration of the unique relationship First Nations youth have with their environment and how it might influence physical activity. The purpose of this study was to explore the physical activity-environment relationship with First Nations youth and develop a conceptual model of this relationship in First Nations communities. Methods: Using the principles of community-based participatory research (CBPR) and Two-Eyed Seeing, First Nations youth (n=14) were trained in the art of Photovoice to take photos of the physical activity environment. Next, the youth took part in a talking circle to share their experience of physical activity opportunities in their community. Talking circles were analysed for themes using NVivo 10. Results: Youth co-researchers indicated that the First Nations community environment influences their physical activity through: 1) Policy, 2) Community and Cultural Events, 3) Infrastructure, 4) the Natural Environment, 5) the Social Environment, 6) Transportation, 7) Physical Activity Programs, 8) Relations and 9) Personal Attributes. Informed by the socio-ecological model, a conceptual model demonstrating how youth physical activity is influenced by the environment was created. Conclusions: This study was the first to explore the physical activity-environment link in First Nations communities from a First Nations youth perspective. Using Indigenous and participatory methodologies helped engage youth in understanding and expressing how their physical activity is impacted by their environment.